Development of preschoolers' spiritual potential by means of folk pedagogy - Svitlana Ivakh; Violeta Horodyska (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
The essence of the concepts of spirituality, morality, religion in the scientific literature is defined in the paper; the goals and tasks of spiritual education of preschoolers are justified; the content of preschoolers' spiritual education in software support of the modern nursery schools is highlighted; folk pedagogy as a means of preschoolers' spiritual development is characterized; methodical recommendations on the usage of folk pedagogy in the preschoolers' spiritual development are developed. The study has proved that the spirituality of every child, his humanity, begins with native home, mother's lullaby, grandmother's stories and fragrant bread among the cherry orchard, parental reliable shoulder and grandfather's advice, trusted friends with their humor, games and entertainment. It is proved in this paper, that folk pedagogy due to the traditions, customs and rituals of national calendar provides the ideals of goodness, morality, aesthetics to preschoolers, and every child having suffered for a beneficial effect of national spiritual treasures, honorably aspires to follow parents, grandparents and ancestors' wills, strengthens their family tree with good deeds. We have proved that spiritual education is held by means of language, song, prayer, fairy-tale, lives of saints and heroes, poetry, festivals, entertainment, etc.